Investigating the beliefs of Saudi females regarding physical activity: a qualitative exploration - Basmah Fehaid H Alharbi; Philip Baker; Toby Pavey; Manal F. Alharbi (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Saudi women have been deprived of equal access to and opportunities for an active lifestyle due to sociocultural restrictions. Using the theory of planned behaviour, this elicitation study aimed to explore the salient beliefs of young Saudi women aged 18–35 regarding physical activity (PA). Methods A descriptive qualitative methodology was utilized using a semi-structured interview. A total of 25 transcribed interviews were coded. Content analysis was used to identify the salient beliefs and to rank-order the beliefs using an adaptation of Burnard’s model. Findings Thirty-five salient beliefs were identified as dominant factors in the decision to engage in PA. The salient beliefs about PA are classified as positive (related to advantages, social approval, and enabling) and negative (related to disadvantages, social disapproval, and barriers). These included behavioural beliefs (concerning physical/psychological well-being and social opportunities), normative beliefs (concerning family, community, international and local media influencers’ expectations), and control beliefs (concerning personal, social, natural, and built environment enablers as well as constraints). Conclusions Due to the elicited beliefs, young women may be able to adopt more active lifestyles and change their inactive behaviour. Addressing negative beliefs can help change their inactive behaviour. Strengthening positive beliefs and facilitators is also beneficial.